Water productivity and poverty in the transboundary river basin of India and Bangladesh: a situation analysis. Project report submitted to IUCN under the project "Water Productivity, Poverty and Food Security?. - Amarasinghe, Upali A.; Sharma, Bharat R. (International Water Management Institute, 2011)
For decades, increasing land productivity was a major driver of improving food security and reducing rural poverty. However, with increasing water scarcities, competing water demand across different sectors, and increasing cost of investments in water resources development require a paradigm shift. Improving the productivity of water use is emerging as a new way of addressing water scarcity while reducing vulnerability and improving income. Increasing both physical and economic water productivities (quantity per drop and value per drop) are central to this approach. The extent to which physical and economic water productivity should be improved is and area and context specific. However, the approach is especially important in areas that are populated with large agriculturally dependent small-holder rural people and areas that experience recurrent droughts and floods and lack access to proper infrastructure. A major part of the Ganga-Brahamaputra-Meghna (MBG) river basins have such characteristics. This report examines the current situation of poverty, food security and water productivity and their linkages and knowledge gaps in the MBG basins.